2014
DOI: 10.14800/ics.269
|View full text |Cite
|
Sign up to set email alerts
|

Adult NK lineage development in humans is strengthened upon emergency

Abstract: Emergency conditions such as infection demand rapid production and activation of innate immune cells to combat noxious extrinsic agents. In mice, pathogen recognition through Toll like receptors (TLR) and the resulting pro-inflammatory cytokine release induce the expansion of bone marrow hematopoietic stem cells and instruct early differentiation fates so immediate innate cell development is guaranteed. Accordingly, recent work suggests that human primitive cell populations are also capable of microbial compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Emergency hematopoiesis defines the production of functional hematopoietic cells under nonhomeostatic, proinflammatory, or biologically stressed conditions [14]. Blood cell production is a tightly regulated process that, after birth and throughout life, starts in a conspicuous hematopoietic stem cell (HSC) subset residing within the bone marrow (BM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency hematopoiesis defines the production of functional hematopoietic cells under nonhomeostatic, proinflammatory, or biologically stressed conditions [14]. Blood cell production is a tightly regulated process that, after birth and throughout life, starts in a conspicuous hematopoietic stem cell (HSC) subset residing within the bone marrow (BM).…”
Section: Introductionmentioning
confidence: 99%
“…According to what mouse research has shown, human multilymphoid progenitors (MLP) are capable of responding to TLR stimulation by producing dendritic cells, and our recent work suggests that primitive early lymphoid progenitor populations are also capable of microbial components discrimination through TLR, a mechanism that mostly facilitates their differentiation to innate lymphoid lineage cells. Of special interest, TLR9 ligation on adult BM progenitors promotes the quick development of NK lineage cells by using mechanisms that involve IL-15R upregulation [4, 9]. …”
Section: Introductionmentioning
confidence: 99%